2002
DOI: 10.1080/00498250210144820
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and disposition of rosuvastatin, a new 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, in rat

Abstract: 1. The pharmacokinetics and disposition of rosuvastatin, a new 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, were investigated following single administration of (14)C-rosuvastatin in the Sprague-Dawley rat. 2. Following oral administration of (14)C-rosuvastatin at 1, 5 and 25 mg kg(-1), the C(max) and AUC of the radioactivity in the plasma increased more than the increase in dose ratio. 3. Excretion of radioactivity was 98.0% of the dose in the faeces and 0.4% in the urine up to 168 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 9 publications
12
35
0
Order By: Relevance
“…The CL renal,p of pravastatin was observed with 14% of total plasma clearance. This is concordant with the report indicating that in rats pravastatin is eliminated from the kidneys as well as the liver (Takada et al, 2004) while other statins are predominantly eliminated from the liver (Boberg et al, 1998;Nezasa et al, 2002;Watanabe et al, 2010). Taken together, these findings indicate that the involvement of Oatps in vivo can be assessed by comparing the nonrenal clearance of test compounds or for compounds with minimal renal excretion by comparing the total clearance between the presence and absence of rifampicin.…”
Section: Discussionsupporting
confidence: 80%
“…The CL renal,p of pravastatin was observed with 14% of total plasma clearance. This is concordant with the report indicating that in rats pravastatin is eliminated from the kidneys as well as the liver (Takada et al, 2004) while other statins are predominantly eliminated from the liver (Boberg et al, 1998;Nezasa et al, 2002;Watanabe et al, 2010). Taken together, these findings indicate that the involvement of Oatps in vivo can be assessed by comparing the nonrenal clearance of test compounds or for compounds with minimal renal excretion by comparing the total clearance between the presence and absence of rifampicin.…”
Section: Discussionsupporting
confidence: 80%
“…The mean steady-state RSV maximum total plasma concentration in humans is ∼50 ng/ ml (0.1 mM) after an 80-mg daily oral dose (Warwick et al, 2000;Cooper et al, 2003). Accumulation (Kp) of total RSV in human and rat hepatocytes in vitro was ∼20-fold in the present study, consistent with previous reports (Nezasa et al, 2003), and ∼20-to 45-fold accumulation in rat liver in vivo (Nezasa et al, 2002), leading to estimated hepatocellular RSV concentrations of #5 mM in humans. At present, the contribution of other transport proteins and passive diffusion to RSV CL BL in SCH cannot be ruled out because specific MRP4 inhibitors have not been identified.…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinsupporting
confidence: 81%
“…Ketoconazole is known to have inhibitory effects on the transport protein P-gp [16]. Active-or facilitated-transport processes may have a role in the absorption and disposition of rosuvastatin [17,18]. The identity of the rosuvastatin transporters that interact with rosuvastatin has not been clearly defined, but if it were a P-gp substrate, an increase in rosuvastatin exposure would be expected following coadministration with ketoconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Active-or facilitated-transport processes may have a role in the absorption and disposition of rosuvastatin. Thus, studies with rats have demonstrated selective hepatic uptake of rosuvastatin by an active transport process [17], and rosuvastatin was shown to be a ligand for a liver-specific human organic-anion-transporting polypeptide present in the basolateral membranes of hepatic cells [18], although the identity of these transporters has not yet been clearly defined. Thus, the results of the present study may provide an indication of whether P-gp-mediated transport contributes to rosuvastatin disposition.…”
Section: Introductionmentioning
confidence: 99%